P423 Pre-exposure prophylaxis as an alternative to PEP for electives. Survey assessing medical students' knowledge and beliefs. (14th July 2019) - Majeed, Zayn; Lee, Hyun; Tayler-Hunt, Pete; Khepar, Kiran Kaur; Wylie, Ann; Mcsorley, John
Abstract : Background: Pre-exposure prophylaxis (PrEP) is indicated for many populations at a higher risk of acquiring HIV through sexual exposure. Healthcare students engaging in medical electives may also be at a higher risk of acquiring HIV through occupational exposure. Since access to post-exposure prophylaxis (PEP) can be variable and costly, PrEP may be a more effective consideration. Methods: We conducted an anonymous online questionnaire assessing knowledge, attitudes and beliefs about PEP, PrEP and HIV risk among medical students at a UK medical school (GKT School of Medical Education) over 6 weeks. Data was collected using the SurveyMonkey™ platform. Results: The response rate was 351/2295 (15.3%). 312/351 (89%) would consider PrEP as an alternative to PEP for their elective if prescribed by a healthcare professional. Of these, 183/312 (59%) would be comfortable obtaining PrEP online. Concerns were around the quality of the medication 84/129 (65%), side effects 57/129 (44%), low perceived risk of HIV exposure 43/129 (33%), efficacy of PrEP 38/129 (29%), drug resistance 26/129 (20%), adherence 19/129 (15%) and cost 15/129 (12%). 276/351 (79%) were aware of PrEP. However, students reported limited knowledge with an average knowledge score of 2.65/5. 48/351 (14%) planned on taking a supply of PEP on elective. 88/351 (25%) were visiting areas with a high HIV prevalence of whom 59 intended to engage in a high-risk specialty. Of the highest risk students, 40/59 (68%) were aware of the high HIV prevalence but only 14/59 (24%) were planning on taking PEP. Conclusion: Medical Students are open to the idea of considering PrEP to reduce their risk of HIV through occupational or sexual exposure. Students report low knowledge of PrEP, and variable knowledge of their individual risks and mitigations. This research indicates a need for robust educational interventions highlighting the benefits of PrEP among medical students and their healthcare advisers. Disclosure: No significant relationships.